Reflexiones respecto al problema de la constitución subjetiva: el psicoanálisis y las (otras) ciencias. // Thoughts on the issue of subjective constitution: psychoanalysis and the (oher) sciences. - Sebastián Andrpes Rojas. (Affectio Societatis, 2010)
This article deals with the link between psychoanalysis and sciences, a relationship that has been historically characterized by a fundamental disagreement. Science criticizes psychoanalysis and questions its value, methods and contributions, by considering that it is a theory without empirical or experimental basis. This is owing to the fact that some of the main theories in psychoanalysis resulting from readings, observation and scientific studies reviews are ignored. As an example of this, we have the psychoanalytic theory about the subjective constitution, which is supported by the studies from experimental psychologists. // El presente artículo reflexiona respecto a la articulación entre el psicoanálisis y las ciencias, relación marcada históricamente por un desencuentro fundamental. La ciencia establece una crítica al psicoanálisis, dudando de su valor, métodos y aportes debido a que lo considera una teoría alejada de lo empírico y la experimentación. Sin embargo, esto se debe a que suele olvidarse que algunas de las principales teorizaciones del psicoanálisis vienen de la lectura, observación y crítica a estudios científicos. Caso ejemplar de lo anterior es la teoría psicoanalítica de la constitución subjetiva, la cual encuentra correlato en los estudios de los psicólogos experimentales.